Between Isothymia and Megalothymia: Addressing Religious-Based Identity Politics in Indonesia - Hidayat, Arfi; Rizkita, Muhammad; Riyanto, Waryani Fajar; Nasih, Sirajun (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This article seeks to analyze the phenomenon of religious politics in Indonesia using Francis Fukuyama's concept of thymos. The 1945 constitution of Indonesia guaranteed the freedom of religion, yet on the one hand, it also provided explanations for six beliefs as definitive religions. This triggers the marginalization of adherents of traditional beliefs, with their rights not fully accommodated by the state. Thymos shape social and political life, and individuals or groups, when feeling that their thymotic needs are not met, may demand political recognition. Fukuyama explains two patterns of thymos: 1) isothymia, referring to the desire for equal recognition in terms of dignity, values, and identity, and 2) megalothymia, representing the desire for recognition as superior. The findings in this article indicate that religious identity politics in Indonesia are reflected through these two patterns of isothymia and megalothymia, evident in the tumultuous journey of marginalized local belief identities and in identity politics directed towards religion-based dominations.